1987
DOI: 10.1254/jjp.43.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of latamoxef on platelet function and prothrombin time in partially nephrectomized rats.

Abstract: Abstract-Latamoxef(daily 100 and 300 mg/kg, i.v.) was injected once a day for 8 days to 75% and 90% nephrectomized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Administration of NMTT itself produced the same effect as its parent anti biotics (6)(7)(8)13). Interestingly, the in vivo effects were also observed when CEZ or CTZ were administered ( (Table 1).…”
Section: Effectmentioning
confidence: 81%
See 2 more Smart Citations
“…Administration of NMTT itself produced the same effect as its parent anti biotics (6)(7)(8)13). Interestingly, the in vivo effects were also observed when CEZ or CTZ were administered ( (Table 1).…”
Section: Effectmentioning
confidence: 81%
“…(1)(2)(3)(4)(5). Subsequent studies demonstrated that the antibiotics-induced hypoprothrombinemia was manifested only in vitamin K-deficient animals and not in rats fed an ordinary diet (6)(7)(8). These results suggest a close corre lation of vitamin K metabolism with the development of adverse effects of antibiotics on the blood coagulation system.…”
Section: Abstract-malementioning
confidence: 99%
See 1 more Smart Citation
“…dZ-( 1/3,5/3)-2-(Phenylsulfonyl)-3-hydroxy-6a,7a-epoxy-2azabicyclo [3.3.0]octane (25). IR (CHClg) 3360,1325,1155 Hz), 5.38-5.67 (1 H, m), 7.36-7.65 (3 H, m), 7.75-8.05 (2 H, m).…”
Section: Dz-czs-2-[2-[(phenylsulfonyl)amino]cyclopent-4-enyl]ethanol ...mentioning
confidence: 99%
“…Epoxidation of 28 proceeded from the sterically less hindered side and compound 29 was obtained as the sole product. These compounds 25 and 29 were also converted to 26a,b and 27 or 30a,b and 31, respectively, by the procedure described for the conversion of 10 to 11a,b and 12.…”
mentioning
confidence: 99%